2011
DOI: 10.1128/aac.01566-10
|View full text |Cite
|
Sign up to set email alerts
|

In VivoandIn VitroAntimalarial Properties of Azithromycin-Chloroquine Combinations That Include the Resistance Reversal Agent Amlodipine

Abstract: Evidence of emerging Plasmodium falciparum resistance to artemisinin-based combination therapies, documented in western Cambodia, underscores the continuing need to identify new antimalarial combinations. Given recent reports of the resurgence of chloroquine-sensitive P. falciparum parasites in Malawi, after the enforced and prolonged withdrawal of this drug, and indications of a possible synergistic interaction with the macrolide azithromycin, we sought to further characterize chloroquine-azithromycin combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 91 publications
(138 reference statements)
3
46
0
Order By: Relevance
“…Alternatively (or in addition), MQ and QN may inhibit PfCRT CQR (e) and/or PfMDR1 (f), and thereby exert part of their antimalarial effect by blocking the physiological functions of these transporters [49,68,75,76,89]. Several resistance-reversers (RR) have been shown to inhibit PfCRT CQR , and the ability to block this form of the protein may underlie the observed increase in the intrinsic antiplasmodial activities of RRs in CQR versus CQS parasites [56,65,69]. Black and green lines indicate transport pathways and red lines denote modes of antimalarial action.…”
Section: Transport Properties Of Pfcrtmentioning
confidence: 99%
“…Alternatively (or in addition), MQ and QN may inhibit PfCRT CQR (e) and/or PfMDR1 (f), and thereby exert part of their antimalarial effect by blocking the physiological functions of these transporters [49,68,75,76,89]. Several resistance-reversers (RR) have been shown to inhibit PfCRT CQR , and the ability to block this form of the protein may underlie the observed increase in the intrinsic antiplasmodial activities of RRs in CQR versus CQS parasites [56,65,69]. Black and green lines indicate transport pathways and red lines denote modes of antimalarial action.…”
Section: Transport Properties Of Pfcrtmentioning
confidence: 99%
“…(Allos, 2001;Anonymous, 2013;Crameri & Heininger, 2008;Jimenez et al, 2015;Mitj a et al, 2015;Rolain et al, 2004;Ruiz et al, 2007;Stoner, 2007;Zuckerman, 2004), and have shown activity against some protozoa such as Plasmodium spp. or Toxoplasma gondii (Lee et al, 2011;Pereira et al, 2011). Additionally, despite not showing good activity against nonfermenter Gram-negative microorganisms such as Pseudomonas, macrolides like azithromycin have demonstrated potential to disaggregate biofilms by this micoorganism, and thus, their synergistic effect together with antipseudomonal antibiotics are currently under study to avoid and eradicate Pseudomonas biofilms (Saini et al, 2015).…”
Section: Clinical Usementioning
confidence: 99%
“…There are some reports on the effects of chloroquine on some species of rodents infected by Plasmodium chabaudi, Plasmodium yoelii and P. berghei [18][19][20] . Since chloroquine and quinine are the most common antimalarial drugs, their therapeutic effects and risk of resistance to drugs were studied.…”
Section: Introductionmentioning
confidence: 99%